Strategies of the National Unity and Politics Agency in Strengthening Religious Harmony - Muh. Hidayat Sultan; Abdul Pirol; Salmilah Salmilah (International Journal of Educational Administration, Management, and Leadership, 2025)
This study explores the strategies implemented by the National Unity and Politics Agency (Bakesbangpol) in strengthening religious harmony and examines the challenges encountered in their application. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis to gain an in-depth understanding of Bakesbangpol’s initiatives. The findings reveal that Bakesbangpol employs a multifaceted approach, including interfaith dialogues, conflict prevention mechanisms, community engagement, and public education campaigns, all aimed at fostering understanding and reducing tensions among diverse religious communities. Interfaith dialogues and the Forum for Religious Harmony (FKUB) play pivotal roles in mediating conflicts and promoting peaceful coexistence. However, the study also identifies significant challenges, such as deep-rooted social prejudices, the spread of misinformation on social media, and resource limitations that hinder the full realization of religious harmony. Despite these obstacles, Bakesbangpol’s efforts have positively impacted community relations, highlighting the importance of proactive and collaborative government-led strategies in managing religious diversity. The study concludes with recommendations to enhance these initiatives through expanded dialogue programs, improved digital literacy, strengthened community engagement, and increased resource allocation to ensure sustainable interfaith harmony.